Introduction to Spiritual Intelligence for Non-Muslim Students at a Higher Learning Institution - Hamzah, Rohana; Mohamad, Ahmad Muhaimin; Latada, Fatmawati; Abdul Rani, Anita; Abdullah, Nur Athiroh Masyaa’il Tan; Abdullah, Christina Andin; Ali, Zarina Mohd (Jurnal Ilmiah Peuradeun, 2024)
The overemphasis on science and technology for economic and national growth, driven by Western influence, has led to the neglect of the intrinsic value of spiritual and social dimensions in education. This issue undoubtedly affects non-Muslim students as well. To address this, the Department of Social Sciences at the Centre for Human Sciences, Universiti Malaysia Pahang Al-Sultan Abdullah, introduces and exposes non-Muslim students to the knowledge of spiritual intelligence. The aim of this study was to examine students’ self-understanding of spiritual intelligence based on test scores for elements of God consciousness, self-transcendence, and self-determination. A total of 209 first-year non-Muslim students participated in this study. Data were analyzed quantitatively using descriptive analysis, mean rank comparison, and correlational analysis. The results from the descriptive analysis indicated that non-Muslim students understood all key concepts in spiritual intelligence. The mean rank comparison showed a significant difference only in the God consciousness element between Hindu students and others. Finally, correlation analysis revealed that all three variables positively correlated with each other. The findings of this study suggest the need to continue efforts to impart the knowledge of spiritual intelligence to non-Muslim students in higher education institutions to improve well-being within society, regardless of race and individual beliefs.